Ogrody Keplera – Ars Electronica 2020 - Myoo , Sidey (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article presents the content shown at the “Festival of Art, Science and Society - Ars Electronica 2020”, which is organized annually in Linz. The focus was on the awarded and distinguished artistic works, taking into account their interpretation and the workshop in which they were created. In the article are presented i.a. such works of art as computer animation, network art, artificial intelligence art, hybrid art or bioart, which was briefly interpreted in relation to the currently being developed technologies and social contexts that accompanies it. The text was written as a result of the author’s personal participation in the festival, which also allowed to take into account the differences between the festival held mostly by web, as it was in 2020, compared to the stationary participation in it, as it was in previous years.